Drug Repurposing Screen for Compounds Inhibiting the Cytopathic Effect of SARS-CoV-2 - Chen, Catherine Z.; Shinn, Paul; Itkin, Zina; Eastman, Richard T.; Bostwick, Robert; Rasmussen, Lynn; Huang, Ruili; Shen, Min; Hu, Xin; Wilson, Kelli M.; Brooks, Brianna M.; Guo, Hui; et al. (Frontiers in Pharmacology, 2021)
Drug repurposing is a rapid approach to identify therapeutics for the treatment of emerging infectious diseases such as COVID-19. To address the urgent need for treatment options, we carried out a quantitative high-throughput screen using a SARS-CoV-2 cytopathic assay with a compound collection of 8,810 approved and investigational drugs, mechanism-based bioactive compounds, and natural products. Three hundred and nineteen compounds with anti-SARS-CoV-2 activities were identified and confirmed, including 91 approved drugs and 49 investigational drugs. The anti-SARS-CoV-2 activities of 230 of these confirmed compounds, of which 38 are approved drugs, have not been previously reported. Chlorprothixene, methotrimeprazine, and piperacetazine were the three most potent FDA-approved drugs with anti-SARS-CoV-2 activities. These three compounds have not been previously reported to have anti-SARS-CoV-2 activities, although their antiviral activities against SARS-CoV and Ebola virus have been reported. These results demonstrate that this comprehensive data set is a useful resource for for drug repurposing efforts, including design of new drug combinations for clinical trials for SARS-CoV-2.